Organic humidity sensing film optimization by embedding inorganic nano-anatase TiO2 powder - Azmer, Mohamad Izzat; Zafar, Qayyum; Qadir, Karwan Wasman; Sulaiman, Khaulah; Bawazeer, Tahani M.; Alsoufi, Mohammad S. (Springer, 2018)
In this work, surface-type humidity sensors with P3HT (organic) and P3HT–TiO2 (organic–inorganic hybrid) active layers have been fabricated. The surface morphology of the humidity active films has been studied by atomic force microscopy, whereas their crystalline structure has been studied by X-ray diffraction. We have aimed at improving the sensing parameters of P3HT-based humidity sensor, by embedding nano-anatase TiO2 powder in pristine organic P3HT moiety. The capacitance versus relative humidity (%RH) response curves of the organic and hybrid humidity sensors have been examined in 30–98%RH range (dark ambient condition, room temperature). In general, an increase in capacitance has been observed in both sensors with the increment in RH level. The observed response of both humidity sensors is believed to be associated with polarization change due to the adsorption of water molecules and transfer of charge carriers due to the formation of charge transfer complexes. The hybrid-based humidity sensor has shown significantly improved humidity-sensing parameters, i.e., fivefold higher sensitivity, with hysteresis reduced to one-third as compared to that of pristine organic humidity sensor. A relatively faster response and recovery time has also been obtained by the hybrid sample.